РЕЦЕНЗІЯ НА МОНОГРАФІЮ НЕМЕТ Т.М. «ПРАВОСЛАВНА ЦЕРКВА НА БУКОВИНІ ТА ЙОЗЕФ ФОН ЧИЖМАН: ЗА ЛАШТУНКАМИ ВІДЕНСЬКОЇ ЦЕРКОВНОЇ ПОЛІТИКИ / ПЕРЕКЛ. З НІМ. ОЛЕГА КОНКЕВИЧА». – МОНОГРАФІЯ. ЧЕРНІВЦІ: НАШІ КНИГИ, 2019. 312 С. - Чучко, Михайло Костянтинович; Chuchko, Mykhaylo; Chuchko, Mykhailo (AKTУАЛЬНІ ПИТАННЯ СУСПІЛЬНИХ НАУК ТА ІСТОРІЇ МЕДИЦИНИ, 2023)
The history of the Orthodox Church in different lands of the former Danubian Habsburg Monarchy, in particular in the territory of the Austrian province of Bukovina, continues to be in the field of scientific interests of scientists from different countries and has not lost its relevance as a research problem. In this context, the monographic work of the Austrian scientist, doctor, professor at the University of Vienna, Fr. Thomas Mark Nemeth "The Orthodox Church in Bukovina and Josef von Chizhman: behind the scenes of the Viennese church policy", which was released in Chernivtsi in 2019, in the publishing house "Our Books" as part of the city's book publishing program named after Burgomaster Anton Kokhanovsky. The monograph of Dr. T. M. Nemeth structures of the Orthodox Church on the territory of the Danube Monarchy, and especially regarding the administration of the Orthodox dioceses in the provinces of Bukovina and Dalmatia, for which, on the basis of his expert findings, in 1873 an imperial decree created the Orthodox Bukovina-Dalmatian Metropolis, the eparchy of the Cesleitan part of the Habsburg Empire. The contribution of Prof. J. von Chizhman in the training of theological personnel for the Orthodox theological faculty. Chernivtsi Franz Josef University, founded in 1875. Having carefully and thoroughly studied the works of researchers from Austria, Greece, Serbia, Romania, Ukraine, Slovakia, etc. countries, the author considered the identified issues through the prism of the personality of the professor-canonist in five thematic sections of the work, based on sources from the archives of Austria, Slovenia, Romania and Ukraine, most of which he introduced into scientific circulation for the first time, which is very valuable for expanding the source. the base of the problem. Dr. T.M.Nemeth's monograph is an independent, innovative study of theoretical and practical value for studying the religious policy of the Habsburgs and the structure of the Orthodox Church in the Danube Monarchy in general and in Bukovina in particular.
THOMAS MARK NEMETH’S MONOGRAPH «THE ORTHODOX CHURCH IN BUKOVINA AND JOSEPH VON CHIZHMANN: BEHIND THE SCENES OF VIENNA'S CHURCH POLITICS / TRANSL. WITH GERM. OLEH KONKEVYCH». – MONOGRAPH. CHERNIVTSI: OUR BOOKS, 2019. 312 p. REVIEW.
РЕЦЕНЗІЯ НА МОНОГРАФІЮ НЕМЕТ Т.М. «ПРАВОСЛАВНА ЦЕРКВА НА БУКОВИНІ ТА ЙОЗЕФ ФОН ЧИЖМАН: ЗА ЛАШТУНКАМИ ВІДЕНСЬКОЇ ЦЕРКОВНОЇ ПОЛІТИКИ / ПЕРЕКЛ. З НІМ. ОЛЕГА КОНКЕВИЧА». – МОНОГРАФІЯ. ЧЕРНІВЦІ: НАШІ КНИГИ, 2019. 312 С.
Буковинський державний медичний університет. Сучавський університет ім. Штефана чел Маре.
Keywords: monograph review, Danubian Habsburg Monarchy, Orthodox Church, J. von Chizhman, Bukovina, Orthodox Bukovina-Dalmatian Metropolis, Chernivtsi Franz Josef University.